2016
DOI: 10.1038/srep18920
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genome evolution and tRNA truncation in Acariformes mites: new evidence from eriophyoid mites

Abstract: The subclass Acari (mites and ticks) comprises two super-orders: Acariformes and Parasitiformes. Most species of the Parasitiformes known retained the ancestral pattern of mitochondrial (mt) gene arrangement of arthropods, and their mt tRNAs have the typical cloverleaf structure. All of the species of the Acariformes known, however, have rearranged mt genomes and truncated mt tRNAs. We sequenced the mt genomes of two species of Eriophyoidea: Phyllocoptes taishanensis and Epitrimerus sabinae. The mt genomes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
46
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 76 publications
8
46
1
Order By: Relevance
“…As expected, the heuristic search did not recover Eupodina (Eupodides) as a clade. Some of the commonly accepted members of Eupodina form a grade with respect to Raphignathina, whereas Eriophyoidea falls outside of Trombidiformes, a result that is consistent with the results of Xue et al (2016Xue et al ( , 2017. Aside from these features and the placement of Hybalicus (Lordalycidae) with several sarcoptiform mites (Grandjeanicus, Oehserchestes and Aphelacarus), the structure and composition of Trombidiformes largely accords with current classification schemes Zhang et al 2011).…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…As expected, the heuristic search did not recover Eupodina (Eupodides) as a clade. Some of the commonly accepted members of Eupodina form a grade with respect to Raphignathina, whereas Eriophyoidea falls outside of Trombidiformes, a result that is consistent with the results of Xue et al (2016Xue et al ( , 2017. Aside from these features and the placement of Hybalicus (Lordalycidae) with several sarcoptiform mites (Grandjeanicus, Oehserchestes and Aphelacarus), the structure and composition of Trombidiformes largely accords with current classification schemes Zhang et al 2011).…”
Section: Resultssupporting
confidence: 72%
“…This is concordant with the results of recent molecular based studies, which place Nematalycidae or Eriophyoidea outside of Trombidiformes (Pepato & Klimov 2015;Xue et al 2016;Xue et al 2017). But note that the constraint for the placement of EN within Trombidiformes (hypothesis 1 of table 4) results in a tree length that is not significantly different to the tree resulting from the unconstrained search (p=0.57: K-H test), and so the position of EN is not yet known.…”
Section: The Phylogenetic Position Of the Eriophyoidea + Nematalycidasupporting
confidence: 78%
See 1 more Smart Citation
“…Furthermore, A. ardeae of the family Pterolichidae showed a sister-group relationship with the family Pyroglyphidae (D. farinae and D. pteronyssinus) (Figure 1). The phylogenetic relationships found in our study are well-congruent with previous mitogenome studies reported by Lee and Wang (2016) and Xue et al (2016).…”
supporting
confidence: 82%
“…Among them, T. pueraricola and T. truncatus are predominant and distributed in different climate zones, providing an opportunity to investigate the potential effect of climate on the evolution of their mitogenome. Both these Tetranychus species are agricultural pests (Ehara and Gotoh, ; Seeman and Beard, ; Xue et al, ). Based on surveys, T. pueraricola is mainly distributed in the southern subtropical zone (in southern China), and T. truncatus is mainly distributed in the moderate temperate zone and warm temperate zone (in northern China).…”
Section: Introductionmentioning
confidence: 99%